Differences In Oral and Dental Health Knowledge Between Undergraduate And Professional Level Students at FKG UNMAS Denpasar - I Nyoman Panji Triadnya Palgunadi; Yudha Rahina; Adnyana Gede Widi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction. Knowledge is a primary factor in behavior establishment. Cognition or knowledge may be obtained naturally or planned through education. Knowledge is influenced by several factors including education level, socio-economic status, environment, and facilities availability of healthcare facilities. A person’s cognition level indicates their capability to obtain and understand health information. It is expected that a higher education level leads to more extensive cognition. A lower education level, however, does not necessarily represent a lower cognition level. Cognition escalation is not entirely gained through formal education, but it may be obtained through informal education as well. The health status of the oral cavity is a major part of general physical health. The health of the oral cavity can be determined through oral hygiene status, as various diseases are initiated by poor dental and oral health. Materials and Methods. The objective of this study was to determine the difference in dental and oral health cognition between undergraduate and professional degree students at the Dental Medicine Faculty of Mahasaraswati University, Denpasar. The study was an analytical study with a cross-sectional approach. Data collection was performed simultaneously at the same time. Fifty-two undergraduate students and 48 professional degree students present during data collection were enrolled as the sample. Respondents were required to fill out the designated dental and oral health cognition questionnaire. Results and Discussion. From the results of data analysis using the Independent T-test, the results obtained p < 0.05 where there is a significant difference in knowledge between undergraduate students and professional level students. Conclusion. The conclusion of the study is that there is a significant difference in oral health knowledge between undergraduate students and professional students at the Faculty of Dentistry, Mahasaraswati University, Denpasar.